2011
DOI: 10.1016/j.cellsig.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin channels in ATP release and beyond: An unexpected rendezvous at the endoplasmic reticulum

Abstract: The pannexin (Panx) family of proteins, which is co-expressed with connexins (Cxs) in vertebrates, was found to be a new GJ-forming protein family related to invertebrate innexins. During the past ten years, different studies showed that Panxs mainly form hemichannels in the plasma membrane and mediate paracrine signalling by providing a flux pathway for ions such as Ca²(+), for ATP and perhaps for other compounds, in response to physiological and pathological stimuli. Although the physiological role of Panxs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 187 publications
3
84
0
1
Order By: Relevance
“…The control of [Ca 2ϩ ] ER requires a tight handling of these mechanisms, because an increase in [Ca 2ϩ ] ER renders cells hypersensitive toward agonist-induced Ca 2ϩ signaling, whereas a decrease in [Ca 2ϩ ] ER may provoke ER stress and the activation of the unfolded protein response (3,4). The passive Ca 2ϩ leak has been one of the most enigmatic paradigms in Ca 2ϩ signaling, given the poor understanding of the molecular mechanisms and candidates responsible for the passive Ca 2ϩ leak (5). Recent work from the laboratories of Reed and Chae (6,7) demonstrated that Bax inhibitor-1 (BI-1) affects passive Ca 2ϩ leak from the ER.…”
Section: The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
See 1 more Smart Citation
“…The control of [Ca 2ϩ ] ER requires a tight handling of these mechanisms, because an increase in [Ca 2ϩ ] ER renders cells hypersensitive toward agonist-induced Ca 2ϩ signaling, whereas a decrease in [Ca 2ϩ ] ER may provoke ER stress and the activation of the unfolded protein response (3,4). The passive Ca 2ϩ leak has been one of the most enigmatic paradigms in Ca 2ϩ signaling, given the poor understanding of the molecular mechanisms and candidates responsible for the passive Ca 2ϩ leak (5). Recent work from the laboratories of Reed and Chae (6,7) demonstrated that Bax inhibitor-1 (BI-1) affects passive Ca 2ϩ leak from the ER.…”
Section: The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
“…2B). The concentrationdependent effects of CTP1 on the Ca 2ϩ leak were obtained by adding different concentrations of CTP1 (5,10,20,40, and 80 M) after 10 min of efflux (Fig. 2C).…”
Section: A C-terminal Peptide Representing the Putative Pore Domain Omentioning
confidence: 99%
“…Connexin (Cx) subunits are the building blocks of vertebrate gap junction channels [110][111][112][113]. More than 20 human connexin isoforms have been identified, with predicted size of individual species ranging from 23 to 62 kDa and, accordingly, referred as to Cxn, where n denotes the molecular weight (e.g., Cx30, Cx43).…”
Section: Connexinsmentioning
confidence: 99%
“…[17][18][19] Pannexins are related to the Cx-protein family: they have a similar topology but no sequence homology with Cxs and form plasma membrane channels that, like Cx-hemichannels, are Ca 2þ -permeable and function as ATP release channels. 20,21 Panx1 is expressed in SMCs of resistance arteries in several vascular beds 22 and plays a role in the vasoconstriction induced by a1-adrenergic stimulation of thoracodorsal arteries. 23, 24 Here we aimed to investigate whether Cx-hemichannels are involved in SMC Ca 2þ oscillations and control of vascular tone.…”
Section: Introductionmentioning
confidence: 99%